2002
DOI: 10.1021/bi011732m
|View full text |Cite
|
Sign up to set email alerts
|

The C-Terminus and Linker Region of S100B Exert Dual Control on Protein−Protein Interactions with TRTK-12

Abstract: S100B, an EF-hand calcium-binding protein composed of two S100beta monomers, undergoes a calcium-dependent conformational change that provides a surface for target interactions. In this study, the calcium-sensitive S100B-binding epitope TRTK-12 has been used to probe the contributions of the linker and C-terminal regions of S100B to protein-protein interactions. These contributions were quantified using C-terminal mutant S100B proteins lacking the C-terminal seven (S100B85stop) or nine (S100B83stop) residues o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
37
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(41 citation statements)
references
References 44 publications
4
37
0
Order By: Relevance
“…This is consistent with the S100B calcium-dependent target recognition mechanism, because the interaction is inhibited by the well characterized target peptide TRTK-12. This peptide, which has the highest affinity for S100B of any known target (76), contains a consensus motif for S100B-binding that is conserved in several mammalian cytoskeletal proteins including tubulin, glial fibrillary acidic protein, and vimentin (13). Further, S100B and S100B-EGFP both produce the filamenting phenotype and show similar co-localization patterns, indicating that the EGFP fusion does not interfere with the target-binding regions in S100B located at its C terminus (helix IV) and linker (76).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is consistent with the S100B calcium-dependent target recognition mechanism, because the interaction is inhibited by the well characterized target peptide TRTK-12. This peptide, which has the highest affinity for S100B of any known target (76), contains a consensus motif for S100B-binding that is conserved in several mammalian cytoskeletal proteins including tubulin, glial fibrillary acidic protein, and vimentin (13). Further, S100B and S100B-EGFP both produce the filamenting phenotype and show similar co-localization patterns, indicating that the EGFP fusion does not interfere with the target-binding regions in S100B located at its C terminus (helix IV) and linker (76).…”
Section: Discussionmentioning
confidence: 99%
“…This peptide, which has the highest affinity for S100B of any known target (76), contains a consensus motif for S100B-binding that is conserved in several mammalian cytoskeletal proteins including tubulin, glial fibrillary acidic protein, and vimentin (13). Further, S100B and S100B-EGFP both produce the filamenting phenotype and show similar co-localization patterns, indicating that the EGFP fusion does not interfere with the target-binding regions in S100B located at its C terminus (helix IV) and linker (76). Sedimentation equilibrium studies have shown that the EGFP moiety neither interferes with S100B dimerization nor causes oligomerization or aggregation of S100B-EGFP.…”
Section: Discussionmentioning
confidence: 99%
“…However, the S100b C-terminal domain is important for certain S100b/target protein interactions. [43][44][45] With this background, one possibility would be that S100b2 interacts with S100b, modulating the neurotrophic biological activities normally associated with the S100b homodimer; (ii) the S100b2 mRNA isoform is finally not translated and is produced to modulate the S100b mRNA pool, available for S100b protein production. Such hypothesis could be supported by the strong correlation existing between the S100b and S100b2 mRNA levels in the brain of AD cases.…”
Section: -42mentioning
confidence: 99%
“…We first studied the interactions of the wild-type S100B and of a C-terminal deleted mutant S100B (S100B⌬Ct) with IQGAP1 and AHNAK. We used S100B⌬Ct because the C terminus domain of S100B is required for interactions between S100B and strict Ca 2ϩ -dependent target protein (32,33). NIH 3T3 cells were transfected with expression vectors encoding S100B or S100B⌬Ct, and complex formation was assayed by co-immunoprecipitation using the N-terminal S100B monoclonal antibody S16 (Fig.…”
Section: Mechanism Of Znmentioning
confidence: 99%